Draft Annual Plan 1989-90 Volume-I Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1989)
Coconut is the main crop of the islands covering 2780 hectres out of the 2785 hectares under Agriculture, Other crops cultivated as intercrops are vegetables, pulses and Fruits. A little sugaraane is cultivated in some lev; lying water loged fields where coconut in not grown, in an area of only 25 hectres, at \ Andrott and Kalpeni. the prsent production of coconut is 23,5 Million nuts which is proposed to be raised to 25 Million nuts at the end of the Seventh Five Year Plan.
Planning Cell Secretariat Lakshadweep